2000
DOI: 10.1007/bf03167637
|View full text |Cite
|
Sign up to set email alerts
|

Do picture archiving and communication systems improve Report turnaround times?

Abstract: Radiology departments are beginning to embrace new technologies to decrease operating budgets and improve services. One of these technologies is the picture archiving and communication system (PACS). PACS, through immediate availability of images to the radiologist, promises to decrease turnaround times of reports to the clinician. The purpose of this study was to determine if this technology actually decreases the time for referring clinicians to receive reports generated by the radiologist. The time to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 2 publications
0
19
0
1
Order By: Relevance
“…Another study found a 9 % improvement in RTAT [126,127]. Yet another study reported that the median PEWT was significantly longer for plain X-rays after PACS implementation: increasing from 20 to 25 min for A&E patients and three to 42 min for patients on intensive care [125].…”
Section: Picture Archival and Communication System (Pacs)mentioning
confidence: 97%
See 2 more Smart Citations
“…Another study found a 9 % improvement in RTAT [126,127]. Yet another study reported that the median PEWT was significantly longer for plain X-rays after PACS implementation: increasing from 20 to 25 min for A&E patients and three to 42 min for patients on intensive care [125].…”
Section: Picture Archival and Communication System (Pacs)mentioning
confidence: 97%
“…Five (9 %) of the 57 included studies evaluated PACS [122][123][124][125][126][127]. The uncontrolled postintervention design was used in one study [123] and the remaining four studies used the pre-and post-intervention design.…”
Section: Picture Archival and Communication System (Pacs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Integration of a PACS into the hospital information system and RIS has an additional positive impact on report turnaround time and communication between physicians (18 -20). On the other hand, Mehta et al (21) found no difference in time to final reports being signed by staff radiologists, but they did find an 85% improvement in time to a preliminary report by a resident or fellow when a PACS system was employed. These authors attributed the results to a relatively persistent, lackadaisical attitude toward signing on the part of staff radiologists.…”
Section: Discussionmentioning
confidence: 95%
“…The transition to soft-copy interpretation via PACS is one technological advance that has been touted as promising increased productivity and improved report turnaround times. [5][6][7] While PACS does provide a technological solution to several shortcomings in traditional film-based workflow, exploiting this technology to achieve improved work efficiency, especially in the academic setting, has been a challenge. Without the proper support in place to allow the radiologist the ability to interpret imaging in this soft-copy environment efficiently, effectively, and without excessive fatigue, the productivity advantages promised by PACS are not realized.…”
Section: Linical Work By Academicmentioning
confidence: 99%